Whole genome sequencing of Castanea mollissima and molecular mechanisms of sugar and starch synthesis - Li, Rongchen; Huang, Xiaolu; Yang, Liping; Liao, Jianming; Wei, Xiaojuan; Li, Junji; Zeng, Guangyu; Liu, Dan; Shi, Zhuogong; Zhao, Zhiheng (Frontiers in Plant Science, 2024)
The chestnut tree exhibits self-incompatibility, where the selection of the male parent (pollen xenia) significantly affects seed starch metabolism, as well as fruit yield and quality. Despite its importance, the molecular mechanisms underlying pollen xenia remains largely unknown. In this study, we utilized the 'Lan You' variety of C. mollissima to construct a high-quality reference genome.. As a result, a first Telomere-to-telomere (T2T) gap-free genome for this species was successfully assembled. A total of 560 transcription factors and 22 structural genes were identified as consistent across the TO-GCNs, indicating a consistent regulation pattern in the co-expression of genes involved in starch accumulation.. These networks were further divided into three sub-networks: T1, T2, and T3. Among these, the T1 and T2 sub-networks exhibited a higher number of structural genes with consistent regulation patterns and were closely associated with sugar biosynthesis. The gene SBE (Camol08G0254600) was identified as the hub gene with the highest degree of connectivity, encoding a key rate-limiting enzyme in the amylopectin biosynthesis pathway. This study provides a foundation for further research on C. mollissima population genetics, genetic improvement, and strategies aimed at enhancing yield and quality.